Axial Vibration Analysis of the Mud Recovery Line on Deepwater Riserless Mud Recovery Drilling System - 王国栋 陈国明 许亮斌 殷志明 (China ocean engineering, 2014)
The series connection of multistage pumping module is the common concept of deepwater riserless mud recovery drilling system. In this system, the influence of the mass of pumping module on the vibration of mud recovery line cannot be ignored, and the lumped mass method has been utilized to discretize the mud recovery line. Based on the analysis of different boundary conditions, the paper establishes the axial forced vibration model of the mud recovery line considering the seawater damping, and the vibration model analysis provides the universal solution to the vibration model. An example of the two-stage pumping system has been used to analyze the dynamic response of mud recovery line under different excited frequencies. This paper has the important directive significance for the application of riserless mud recovery drilling technology in deepwater surface drilling.